Strategi Pengawasan Bawaslu Deli Serdang Pada Pemilu Tahun 2024 - Aminuddin; Ridwan Nasution (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2021)
The General Election and Regional Head Election (Pilkada) will be held in 2024. As the organizer of the Regency election, the Deli Serdang Bawaslu is responsible for overseeing elections that are carried out at all stages, including planning, preparation, implementation, and evaluation to ensure the creation of democracy quality. There are several strategies that will be launched by Deli Serdang Bawaslu in supervising the 2024 elections, namely the provision of Online Reporting (SIWASLU Application), provision of Google Forms, Citizens Forum, Monitoring Corner, and forming a School of Participatory Supervision Cadres (SKPP). In order for this strategy to work well, the Deli Serdang Bawaslu is constantly trying to collaborate between election organizers, election participants, stakeholders, the community, mass media and community organizations in maintaining the quality of clean and fair elections.